Crystal data for O=DZP - Rocha, Mariana (2018)
The Hirshfeld surface analysis is a well-known method to investigate in detail the characteristics of the crystal packing, such as polymorphism and other aspects of supramolecular assembly. Different functions describe specific properties of the Hirshfeld surface (dnorm, shape index, or curvedness) allowing for intuitive recognition and visual analysis of interactions between molecules. All distances to the Hirshfeld surface (di and dₑ) can be summarized in the form of two-dimensional diagrams (2D fingerprint plots), whose shapes are typical for certain close contacts environment. 2D fingerprint plots were used for decoding and quantifying the intermolecular interactions in the crystal lattice. Hirshfeld surfaces and their associated 2D fingerprint plots were performed using the CrystalExplorer17 program. The O=DZP structural parameters were taken from the CIF file. The 3D dnorm (normalized contact distance) surfaces were mapped over a fixed color scale of −0.135 au (red) to 0.460 au (blue). The 2D fingerprint plots were displayed by using the translated 0.6−2.6 Å range and including reciprocal contacts. Quantum chemical calculations were performed using the Gaussian 03 program. The X-ray structure coordinates were used as starting parameters for geometry optimization at the B3LYP/6-311++G(d,p) level of theory. Vibrational frequencies were calculated to confirm the proper convergence to energy minima on the potential energy surface. The potential energy distribution was calculated with the VEDA4 program. For the electronic spectra, time-dependent density functional theory (TDDFT) method at B3LYP/6-311++G(d,p) approximation was used to compute energies and intensity of 20 lowest energy singlet to singlet electronic excitations in solution (ethanol and toluene) using PCM. NBO analysis, as implemented in the Gaussian 03 package, was performed at the B3LYP/6-311++G(d,p) level for the monomeric and for dimeric structures of the O=DZP molecule, in order to obtain second-order donor → acceptor interaction energies. The AIM2000 program was applied for the topological analysis of selected dimers identified from the crystal structure of O=DZP. To evaluate the nature of different intra- and intermolecular interactions, some topological parameters such as electron density (ρ), the Laplacian electron density (∇²ρ), local potential energy density (V), and kinetic energy density (G) at the bond critical points (BCPs) were calculated adopting the geometry of the crystal structure with normalized hydrogen positions at B3LYP/6-311++G(d,p) approximation. The energies of the intra- and intermolecular interactions were estimated using the formula proposed by Espinosa and coworkers. The molecular electrostatic potential (MEP) of the ketoenamine tautomeric form has also been calculated at the same level of theory.